School nutrition laws in the US: do they influence obesity among youth in a racially/ethnically diverse state? - Sanchez-Vaznaugh, Emma V; Matsuzaki, Mika; Braveman, Paula; Acosta, Maria Elena; Alexovitz, Kelsey; Sallis, James F; Peterson, Karen E; Sánchez, Brisa N (International Journal of Obesity, 2021)
Little is known about the separate or combined effects of state and national nutrition policies regulating food and beverages in schools on child overweight/obesity (OV/OB) and related racial/ethnic disparities. We investigated the influence of school nutrition policies enacted in California, independently and in combination with the United States' national policy "Healthy Hunger Free Kids Act" (HHFKA) on childhood OV/OB and racial/ethnic disparities. An interrupted time series design was used with data from 12,363,089 child-level records on 5th- and 7th-graders in California public schools to estimate sex- and racial/ethnic-specific time trends in OV/OB prevalence during three periods: before the California nutrition policies (2002-2004); when only California policies were in effect (2005-2012); and when they were in effect simultaneously with HHFKA (2013-2016). Before the state's policies, OV/OB prevalence increased annually among children in most subgroups. Improvements in OV/OB trends were observed for almost all groups after the California policies were in effect, with further improvements after the addition of HFFKA. The total change in annual log-odds of OV/OB, comparing the periods with both state and federal policies versus no policies, ranged from -0.08 to -0.01 and varied by grade, sex, and race/ethnicity. Within each sex and grade, the greatest changes were among African-American (-0.08 to -0.02, all p < 0.05) followed by Latino children (-0.06 to -0.01, all p < 0.05). Although disparities narrowed among these groups versus White children after the dual policy period, disparities remained large. State and national nutrition policies for schools may have contributed to containing the upward trend in childhood OV/OB and racial/ethnic OV/OB disparities within California. However, sizable OV/OB prevalence and disparities persist. To end the epidemic, promote healthy weight and increase health equity, future efforts should strengthen state and national policies to improve food quality in schools, particularly those serving populations with the highest OV/OB prevalence.